Academic integration and the media resource library : a case study of the Jurong Institute. - Chua, Chiew Yong. (2008)
This dissertation explores the academic integration of the Media Resource Library programme into the school's curriculum. Collaboration with classroom teachers enhances the library collection and programme to support research, teaching and learning needs more effectively and efficiently.